Analysing the impacts of FDI, material footprint and ICT on the load capacity factor in sub-saharan African countries - Ganda, Fortune (Frontiers in Environmental Science, 2024)
This study explores how foreign direct investment (FDI), material footprint, economic growth, and information and communication technology (ICT) influence the load capacity factor (LCF) in 37 Sub-Saharan African (SSA) countries. The analysis leverages data spanning 1970 to 2019 and employs a range of robust econometric techniques (FM-OLS, D-OLS, DSUR). The findings reveal a surprising yet significant positive association between material footprint and LCF. Conversely, economic growth, FDI, and ICT all exhibit negative relationships with LCF. Interestingly, a causal analysis suggests that these variables -ICT, material footprint, and economic growth have a two-way influence on LCF, meaning they both affect and are affected by it.These insights highlight the complex interplay between economic development, material footprint, and technological advancement in shaping SSA's LCF. The study concludes by offering clear policy recommendations for SSA countries aiming to optimize their LCF.